Clinical, laboratory and immunohistochemical characterization of in situ pulmonary arterial thrombosis in fatal COVID-19. Issue 219 (November 2022) - Quartuccio, Luca; Sonaglia, Arianna; Casarotto, Letizia; McGonagle, Dennis; Di Loreto, Carla; Pegolo, Enrico
Abstract: Background: COVID-19 patients carry an increased rate of thrombosis. It is controversial to which extent thrombi in the pulmonary arterial tree really contribute to disease severity with hypoxemia secondary to microvascular/lung parenchymal damage with viral alveolitis considered to play the main role in critical disease. Objectives: The primary objective was to compare post-mortem lung disease from fatal COVID-19 pneumonia in patients with macroscopically evident pulmonary arterial tree thrombosis and patients without, by characterizing the immunohistochemical nature of thrombi, and by comparing clinical and laboratory features of these patients with other COVID-19 patients who died but without evidence of pulmonary arterial thrombosis (controls). Patients and methods: 13 COVID-19 pneumonia cases (mean age ± standard deviation: 74 ± 6.5 years) with macroscopically visible pulmonary arterial thrombosis were compared to 14 controls. Hematoxylin and Eosin stained slides were reviewed choosing those with visible pulmonary thrombi which were further characterized by immunohistochemistry, in particular for the inflammatory infiltrates. Ante mortem serum markers relevant to pulmonary embolism were evaluated in both groups. Results: Twenty arterial thrombi (5 cases with multiple thrombi) were selected for study and were composed by white blood cells (WBC) [median, IQR range: 10 % (5–12.25)], mainly neutrophils [58 % (35.2–64.5)]. Cases with thrombosis showed significantly higher levels of platelet count [median, IQR range: 195000/mmc (157750–274, 500) vs 143, 500 (113000–175, 250), p = 0.011], LDH [854 U/L (731–1315) vs 539 (391.5–660), p = 0.003] at admission, and D-dimer at ICU transfer [25, 072 FEU (6951–50, 531) vs 1024 (620–5501), p = 0.003]. Conclusions: Immunothrombotically driven arterial thrombi in COVID-19 patients are associated with D-Dimer and LDH elevations, thus linking inflammation, coagulopathy and organ damage in fatal COVID-19.